2003
DOI: 10.1038/ni970
|View full text |Cite
|
Sign up to set email alerts
|

Leukotriene B4 receptor BLT1 mediates early effector T cell recruitment

Abstract: Leukotriene B4 (LTB4) was originally described as a potent lipid myeloid cell chemoattractant, rapidly generated from innate immune cells, that activates leukocytes through the G protein-coupled receptor BLT1. We report here that BLT1 is expressed on effector CD4+ T cells generated in vitro as well as in vivo when effector T cells migrate out of the lymphoid compartment and are recruited into peripheral tissues. BLT1 mediated LTB4-induced T helper type 1 (T(H)1) and T(H)2 cell chemotaxis and firm adhesion to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
322
0
7

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 371 publications
(341 citation statements)
references
References 53 publications
12
322
0
7
Order By: Relevance
“…LTs induce leukocyte recruitment to an inflammatory site both by stimulating chemotaxis and by promoting firm adhesion to endothelial cells. LTB 4 has long been known to induce neutrophil migration in vivo and in vitro (37), and is now recognized to participate in the in vivo trafficking of CD4 and CD8 T lymphocytes (38). cysLTs participate in dendritic cell trafficking to sites of Ag stimulation (39) as well as to lymph nodes (40).…”
Section: Antimicrobial Effector Functions Of Ltsmentioning
confidence: 99%
“…LTs induce leukocyte recruitment to an inflammatory site both by stimulating chemotaxis and by promoting firm adhesion to endothelial cells. LTB 4 has long been known to induce neutrophil migration in vivo and in vitro (37), and is now recognized to participate in the in vivo trafficking of CD4 and CD8 T lymphocytes (38). cysLTs participate in dendritic cell trafficking to sites of Ag stimulation (39) as well as to lymph nodes (40).…”
Section: Antimicrobial Effector Functions Of Ltsmentioning
confidence: 99%
“…LTB 4 acting through its receptors (BLT1) can cause chemotaxis, degranulation, adhesion and enhance the survival of neutrophils. Although BLT1 was long known to be a neutrophil chemoattractant receptor, recent studies identified BLT1 expression on macrophages [22], smooth muscle cells [23], endothelial cells [24], activated T-cells [25] and mast cells [26] considerably expanding the potential role of LTB 4 . Recent experiments from our laboratory demonstrated functional expression of BLT1 on both mature and immature dendritic cells and having a direct effect in the control of adaptive immune responses [27].…”
Section: Leukotriene B 4 and Its Receptorsmentioning
confidence: 99%
“…LT-Rs are expressed on multiple target cells, including leukocytes, smooth muscle cells, and ECs (1). Recent studies implicate the 5-LO pathway in cardiovascular disease (11)(12)(13)(14)(15)(16)(17).Considerable information is available on cysLT 1 -R, whereas little is known about cysLT 2 -R. We have used human umibilical vein (HUV)ECs as a model of vascular cells to study cysLT 2 -R activation by demonstrating that cysLTs exclusively signal through cysLT 2 -R in this cell type (18): In fact, HUVECs are the first primary cell type that selectively expresses cysLT 2 -R. In the study detailed below, we determined HUVEC gene signatures in response to LTD 4 and characterized the resulting phenotypes. LTD 4 responses were compared with those of the prototype vasoactive agonist thrombin, which, in HUVEC, acts through protease-activated receptor (PAR)-1 (19).…”
mentioning
confidence: 99%